1978
DOI: 10.1136/gut.19.7.664
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour gastric acidity after vagotomy.

Abstract: SUMMARY Twenty-four hour intragastric pH during normal daily activity has been studied by nasogastric intubation and aspiration of gastric samples in seven patients four years after vagotomy (four truncal, three selective). Two of these patients also had pre-and early postoperative studies. Mean pH was inversely correlated with basal, insulin-and pentagastrin-stimulated acid outputs. However, one of four patients after truncal vagotomy with drainage, and two of three after selective vagotomy and drainage had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
0
1
Order By: Relevance
“…From experiments testing P-blocking agents, propranolol (a p,and p,-blocker), and practolol (predominantly a p,-blocker), it could be concluded that the sympathomimetic influence on gastric acid secretion involves @,-receptors. This is contrary to the findings of McCloy et al ( 17), who saw no effect of propranolol on histamine-induced gastric acid secretion.…”
contrasting
confidence: 57%
“…From experiments testing P-blocking agents, propranolol (a p,and p,-blocker), and practolol (predominantly a p,-blocker), it could be concluded that the sympathomimetic influence on gastric acid secretion involves @,-receptors. This is contrary to the findings of McCloy et al ( 17), who saw no effect of propranolol on histamine-induced gastric acid secretion.…”
contrasting
confidence: 57%